A New Class of Lasing Materials: Intrinsic Stimulated Emission from Nonlinear Optically Active Metal-Organic Frameworks - Medishetty, Raghavender (2017)
Blue-color stimulated emission with low threshold power is observed from In- and Zn-MOFs, which feature a highly fluorescent chromophore densely packed and rigidly linked to the metal-ion centers in the solid state. The density-of-states and transition dipole moments are calculated and the stimulated emission phenomenon is correlated with these properties.